Gendered Lenses: Women in the News Photography of the 2019 Riau Forest Fires - Anis, Elis Zuliati; Hakim, Lukman (UIN Sunan Kudus, 2025)
This study critically examines the visual representation of women in the news photography of the Riau Pos during the 2019 forest fires, addressing a gap in disaster media research on gendered imagery in Indonesia. Although environmental crises have received scholarly attention, the depiction of women in regional Indonesian newspapers remains underexplored. Using a qualitative methodology that combines visual semiotic analysis and Critical Discourse Analysis, the study explores how women are portrayed across four thematic roles: responders, victims, activists, and religious participants. Our findings demonstrate that while women are increasingly visible in disaster news, their portrayal is consistently shaped by traditional gender norms. Images that suggest female agency are frequently accompanied by captions or articles that reframe this visibility within roles of caregiving, motherhood, or moral virtue. Even in politicized or public contexts, women’s participation is legitimized only when aligned with culturally sanctioned femininity. As a result, their presence is symbolically acknowledged but not discursively empowered. By situating these localized visual practices within broader frameworks of representation and gender discourse, this study advances research in disaster communication, feminist media studies, and Indonesian journalism. It underscores the importance of analyzing how visual media not only reflects, but actively constructs socio-political boundaries of gendered participation in times of crisis, with implications for more equitable disaster risk communication.